Poisoner in chief [compact disc, unabridged] : Sidney Gottlieb and the CIA search for mind control - Kinzer, Stephen (Macmillan Audio, 2019)
The visionary chemist Sidney Gottlieb was the CIA's master magician and gentle-hearted torturer. As head of the MK-ULTRA mind control project, he directed brutal experiments at secret prisons on three continents. He made pills, powders, and potions that could kill or maim without a trace, including some intended for Fidel Castro and other foreign leaders. He paid prostitutes to lure clients to CIA-run bordellos, where they secretly dosed with mind-altering drugs. His experiments spread LSD across the United States, making him a hidden godfather of the 1960s counterculture. For years he was the chief supplier of spy tools used by CIA officers around the world.